Asian migrants and religious experience : from missionary journeys to labor mobility - Brown, Bernardo E.; Yeoh, Brenda S. A. (Amsterdam : Amsterdam University Press, 2018)
Typically, scholars approach migrants' religions as a safeguard of cultural identity, something that connects migrants to their communities of origin. This ethnographic anthology challenges that position by reframing the religious experiences of migrants as a transformative force capable of refashioning narratives of displacement into journeys of spiritual awakening and missionary calling. These essays explore migrants' motivations in support of an argument that to travel inspires a search for new meaning in religion.
Human mobility as engine of religious change / Bernardo E. Brown, Brenda S.A. Yeah -- Saving yogis : spiritual nationalism and the proselytizing missions of global yoga / Amanda Lucia -- Renewed flows of ritual knowledge and ritual affect within transnational networks : a case study of three ritual events of the Xinghua (Henghua) communities in Singapore / Kenneth Dean -- Liberalizing the boundaries : reconfiguration of religious beliefs and practice amongst Sri Lankan immigrants in Australia / Jagath Bandara Pathirage -- From structural separation to religious incorporation : a case study of a transnational Buddhist group in Shanghai, China / Weishan Huang -- "10/40 Window" : Naga missionaries as spiritual migrants and the Asian experience / Arkotong Longkumer -- Religion, masculinity, and transnational mobility migrant catholic men and the politics of evangelization / Ester Gallo -- Helping the wounded as religious experience the free Burma rangers in Karen State, Myanmar / Alexander Horstmann -- A multicultural church : notes on Sri Lankan transnational workers and the migrant chaplaincy in Italy / Bernardo E. Brown -- "Bahala Na Ang Diyos" : the paradox of empowerment among Filipino Catholic migrants in South Korea / Bubbles Beverly Neo Asor -- Feeling Hindu : the devotional Sivaist esthetic matrix and the creation of a diasporic Hinduism in North Sumatra / Silvia Vignato -- What makes Aian migrants' religious experience Asian? Janet Alison Hoskins.
Includes bibliographical references (pages 315-340) and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Asia -- Emigration and immigration -- Religious aspects -- Congresses; Immigrants -- Asia; Immigrants -- Religious life; Emigration and immigration -- Religious aspects; Asia; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Regional Studies; SOCIAL SCIENCE / Sociology / General; RELIGION / General; Conference papers and proceedings; Electronic books